Intimate partner violence: The need for an alternative primary preventive approach in Botswana - Radiance M. Ogundipe; Nataly Woollett; Gboyega Ogunbanjo; Anthony A. Olashore; Stephane Tshitenge (AOSIS, 2018)
Intimate partner violence is a common social problem which causes considerable relationship stress and results in significant morbidity and mortality of the victims. Botswana, like many other countries in sub-Saharan Africa, has tried to address the problem of intimate partner violence with legislations prescribing punitive measures for the perpetrators and protection for the victims. The effectiveness of these measures in reducing the prevalence of intimate partner violence is doubtful. This article is to motivate for an alternative primary preventive approach to the problem as a more pragmatic option.